Efficacy of antifungal PACT in an in vitro model of onychomycosis. (24th March 2014) - Mehra, T.; Schaller, M.; Walker, B.; Braunsdorf, C.; Mailänder‐Sanchez, D.; Schynowski, F.; Hahn, R.; Röcken, M.; Köberle, M.; Borelli, C.
Abstract Background The difficulty of antifungal substances to penetrate keratin and slow nail growth limit the efficacy of topical therapy in onychomycosis. One promising alternative is photodynamic antimicrobial chemotherapy, or PACT: an irradiated photosensitizer creates singlet oxygen molecules which destroy pathogens without damaging human cells. Objective As PACT has demonstrated strong antifungal capabilities, we wanted to investigate its efficacy in an in vitro model of onychomycosis. Methods PACT was tested in a microdilution assay, in an in vitro onychomycosis model as well as in a patient. Results PACT inhibited fungal growth in the microdilution assay with no colonies of T. rubrum detectable. Fungal growth was also inhibited in an onychomycosis model, after 30 min of LED irradiation. Subsequently, a patient with distolateral onychomycosis was treated on three consecutive days and showed significant and durable improvement of nail morphology 6 months after. Conclusion PACT appears to be an effective treatment of onychomycosis in vitro. The promising results need to be validated by clinical trials.